Formulasi Serbuk Effervescent Limbah Tulang Ikan Bandeng (Chanos chanos) sebagai Supplement Kalsium Tulang: Formulation Effervescent Powder form of Milk Fish (Chanos chanos) Bone Waste as a Calcium Supplement - Hilmiati Wahid; Andi Juaela Yustisi; Prayitno Prayitno; Aninditya Dwi Lestari Amir (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Milkfish fish bone (Chanos chanos) is a fish with a high calcium consumption of 23.99%. This high level of calcium means that the waste of milkfish bones can be used as a bone supplement in the form of effervescent powder. to meet the intake of calcium supplements in maintaining health. This study aims to determine the physical and chemical stability of the effervescent powder from milkfish bone waste. The research method was calcium from milkfish bone meal analyzed using an Atomic Absorption Spectrophotometer and made in the form of effervescent powder with concentrations of 800 mg, 900 mg and 1000 mg. Examination of the preparations included organoleptic tests, pH tests, water content tests, flow rate tests, hedonic tests. The results for the organoleptic test did not change. The results of the solubility test, flow rate, pH test, water content test experienced an increase in value before and after the cycling test. The results of the F2 hedonic test favored the shape and color. It can be concluded that the calcium concentration of fish bone powder is 243121 mg/kg. Milkfish bone powder can be formulated in the form of effervescent powder as a bone calcium supplement that is physically and chemically stable Kata Kunci: Waste of Milkfish Bones, Effervescent Powder, Calcium Abstrak Tulang ikan Bandeng (Chanos chanos) adalah ikan konsumsi berkalsium tinggi sebesar 23,99%. Tingginya kadar kalsium ini sehingga limbah tulang ikan bandeng dapat dimanfaatkan menjadi suplemen tulang dalam bentuk serbuk effervescent. untuk memenuhi asupan supplement kalsium dalam menjaga kesehatan. Penelitian ini bertujuan untuk mengetahui sediaan serbuk effervesent limbah tulang ikan bandeng yang stabil secara fisika dan kimia. Metode penelitian yaitu kalsium tepung tulang ikan bandeng dianalisis menggunakan Spektrofotometer Serapan Atom dan dibuat dalam bentuk sediaan serbuk effervescent dengan konsentrasi 800 mg, 900 mg dan 1000 mg. Pemeriksaan terhadap sediaan meliputi uji organoleptik, uji pH, uji kadar air, uji kecepatan alir, uji hedonik. Hasil penelitian untuk uji organoleptik tidak mengalami perubahan. Hasil uji waktu larut, kecepatan alir, uji pH, Uji Kadar air mengalami peningkatan nilai sebelum dan sesudah cycling test. Hasil uji hedonik F2 disukai dari bentuk dan warna. Dapat disimpulkan konsentrasi kalsium serbuk tulang ikan sebesar 243121 mg/kg. Serbuk tulang ikan bandeng dapat diformulasikan dalam bentuk sediaan serbuk effervescent sebagai supplement kalsium tulang yang stabil secara fisika dan kimia. Kata Kunci: Limbah Tulang Ikan Bandeng, Serbuk Effervescent, Kalsium